Analisis Perspektif dan Sikap Dosen, Mahasiswa, dan Tendik Tingkat Universitas di Universitas Djuanda Bogor - La Ode Amril; Siti Pupu Fauziah; Arti Yoesdiarti; Resti Yekstyastuti; Syaima Lailatul Mubarokah (UHN IGB Sugriwa Denpasar, 2022)
This study aims to analyze the understanding, interests and perspectives of lecturers, students and education staff on MBKM activities and analyze the impact of MBKM implementation on lecturers, students and staff as a measure of the success of the MBKM program at Djuanda University. The research was conducted on 15 - 20 December in seven (7) undergraduate faculties at the University of Djuanda Bogor. Data collection was carried out using the census method. Data were analyzed using descriptive statistics. The results of the analysis show that the understanding of lecturers, students and staff related to MBKM activities is quite good. The interest of lecturers, students and staff is also quite good. The perspectives of lecturers, students and students obtained are quite good and the implementation of MBKM has a good impact on the competence of lecturers and students both on hard-skills and soft-skills of students.